Complications of hip-joint arthroplasty - Filipenko, Volodymyr; Tankut, Volodymyr; Tankut, Olexiy; Zhygun, Anatoliy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article presents results of hip joint arthroplasty for two periods: I – 1968–1994 and II – 1995–2005 (2,798 operations). The basic types of complications, which required repeated surgical interferences, are analysed. Three basic groups of factors, which influenced the development of the above complications, are formulated. The observance of the suggested methods of prophylaxis enabled the authors, during the remote postoperative period, to improve good results from 73 % to 89 % and decrease unsatisfactory ones from 10 % to 3 %.